Proceedings of the Annual PL/DARPA Seismic Research Symposium (13th), Held in Keystone, Colorado on 8-10 October 1991 - Lewkowicz, James F.; McPhetres, Jeanne M. (1991)
In its capacity as a technical agent, the PL's Solid Earth Geophysics Branch manages the DARPA Nuclear Monitoring Research Office's and its own Air Force funded basic research program in verification seismology. The scientific objectives of these programs are to improve the Air Force's capability to seismically detect, locate, identify and estimate the yield of underground nuclear explosions. The purpose of this symposium is to provide the sponsoring agencies an opportunity to review the research accomplished during the preceding year and outline areas of investigation for the coming year. The papers include studies on regional seismic wave propagation, attenuation and scattering, array processing and seismic techniques of yield estimation. Partial contents: Overview of Eurasian seismic stations and networks; Yield estimation, free- surface interactions, and tectonic release at Novaya Zemlya; Lg as a yield estimation tool; The Norilsk DSS profile in northern Siberia--Interpretation of the velocity structure and comparison with basin and range and New England profiling results; Influence of the lower crustal structure on the early coda of regional seismograms; Attempt at waveform modelling--Influence of the superficial geological structure; Single-station estimates of crust and upper mantle velocity structure at broadband IRIS/IDA stations in the USSR.